One-pot synthesis of Bi-reduced graphene oxide composite using supercritical acetone as anode for Na-ion batteries - Hwang, Jieun; Park, Jae-Ho; Chung, Kyung Yoon; Kim, Jaehoon (ELSEVIER SCIENCE SA, 2020)
A high-energy-density Bi-reduced graphene oxide (Bi-RGO) composite was synthesized using the quick one-pot supercritical acetone (scACT) method. The unique deoxygenation properties and ultrafast particle formation in scACT led to the simultaneous reduction of graphene oxide to reduced graphene oxide (RGO) and the formation of heterogeneously nucleated, nanosized Bi particles 10-20 nm in size that were tightly anchored to the basal plane of RGO and homogeneously nucleated, large Bi particles 250-950 nm in size. When tested as the anode of Na-ion batteries, the Bi-RGO composite delivered the high reversible capacity of 200 mAh g(-1) at 50 mA g(-1) and the high volumetric capacity of 60 Ah L-1. In situ X-ray diffraction analysis revealed that the two-step alloying-dealloying Bi -> NaBi -> hexagonal Na3Bi or cubic Na3Bi reactions depended on the Bi particle size.
Keywords: ENHANCED ELECTROCHEMICAL PERFORMANCE; FACILE SYNTHESIS; CATALYTIC COMBUSTION; DIESEL SOOT; SODIUM; WATER; NANOPARTICLES; LI4TI5O12; BISMUTH; MICROSPHERES